2021
DOI: 10.1002/jsfa.11607
|View full text |Cite
|
Sign up to set email alerts
|

Loss of bioactive microRNAs in cow's milk by ultra‐high‐temperature treatment but not by pasteurization treatment

Abstract: BACKGROUND Milk microRNA (miRNA) with bioactivity is beneficial for human health. However, the effect of heat treatment on miRNA in milk is still not clear. In this study, the miRNAs in raw (RM), pasteurized (PM) and ultra‐high‐temperature (UHT) milk (UM) from the same batch were extracted, sequenced and analyzed. RESULTS The results showed that there was a significant difference in miRNAs between RM and UM, but not between RM and PM. The total read counts of milk miRNAs were significantly decreased by heat tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 37 publications
(115 reference statements)
1
14
0
Order By: Relevance
“…Pasteurization of milk was introduced as an unproven technology without prior scientific information of its long-term effects on human health. Pasteurization combined with refrigeration allowed the large-scale introduction of milk's epigenetic signaling machinery into the human food chain, recently promoted as a nutritional and therapeutic opportunity [628] . In contrast to UHT processing of milk, milk EV-derived miRs survive pasteurization, as recently confirmed [629] .…”
Section: Discussionmentioning
confidence: 99%
“…Pasteurization of milk was introduced as an unproven technology without prior scientific information of its long-term effects on human health. Pasteurization combined with refrigeration allowed the large-scale introduction of milk's epigenetic signaling machinery into the human food chain, recently promoted as a nutritional and therapeutic opportunity [628] . In contrast to UHT processing of milk, milk EV-derived miRs survive pasteurization, as recently confirmed [629] .…”
Section: Discussionmentioning
confidence: 99%
“…About 7,000-10,000 years ago, Neolithic humans started to exploit milk from other mammalian species (89), but consumed preferentially fermented milk (89,90), which compared to raw milk contains diminished quantities of bioactive MEX miRs (91). Bovine MEX miRs are conserved by pasteurization of cow milk (72-78 ℃, for >15 s), allowing their delivery into the human food chain (92,93).…”
Section: Physiological Versus Artificial Mex Mir Signalingmentioning
confidence: 99%
“…Consumption of unfermented milk during pregnancy is associated with fetal weight gain and higher birth weight (94)(95)(96)(97)(98), an indicator of fetal growth related to placental weight (99). In contrast to fermented milk with degraded MEX (93), raw and pasteurized milk deliver bioactive MEX including miR-21 and miR-148a (11,29,92,93,100,101). Following oral gavage of bovine MEX to mice, miR-21 and miR-30d accumulated in murine placenta and embryos (35).…”
Section: Bovine Mex Mir Exposure During Pregnancymentioning
confidence: 99%
See 1 more Smart Citation
“…So far, only a few studies have explored whether humans can absorb a meaningful amount of certain exosomal miRNAs from cow’s milk. The findings indicated that milk-derived miRNAs in pasteurized milk are absorbed by adults in meaningful amounts, and moreover, that endogenous miRNA synthesis cannot compensate for dietary deficiency ( Baier et al, 2014 ; Zhang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%